Sorting out Co-occurrence of Rare Monogenic Retinopathies: Stargardt Disease Co-existing with Congenital Stationary Night Blindness. (March 2014) - Huynh, Nancy; Jeffrey, Brett G.; Turriff, Amy; Sieving, Paul A.; Cukras, Catherine A.
Abstract Background: Inherited retinal diseases are uncommon, and the likelihood of having more than one hereditary disorder is rare. Here, we report a case of Stargardt disease and congenital stationary night blindness (CSNB) in the same patient, and the identification of two novel in-frame deletions in the GRM6 gene. Materials and Methods: The patient underwent an ophthalmic exam and visual function testing including: visual acuity, color vision, Goldmann visual field, and electroretinography (ERG). Imaging of the retina included fundus photography, spectral-domain optical coherence tomography (OCT), and fundus autofluorescence. Genomic DNA was PCR-amplified for analysis of all coding exons and flanking splice sites of both the ABCA4 and GRM6 genes. Results: A 46-year-old woman presented with recently reduced central vision and clinical findings of characteristic yellow flecks consistent with Stargardt disease. However, ERG testing revealed an ERG phenotype unusual for Stargardt disease but consistent with CSNB1. Genetic testing revealed two previously reported mutations in the ABCA4 gene and two novel deletions in the GRM6 gene. Conclusions: Diagnosis of concurrent Stargardt disease and CSNB was made on the ophthalmic history, clinical examination, ERG, and genetic testing. This case highlights that clinical tests need to be taken in context, and that co-existing retinal dystrophies and degenerations should be considered when clinical impressions and objective data do not correlate.